Development of Learning Application for Building a Computer in Virtual Reality - Zahir Subakhir,; Mohd Norasri Ismail, (Applied Information Technology And Computer Science, 2023)
Abstract: Virtual Reality (VR) technology has recently been used in several industries to simulate any imaginable 3D object. VR technology is also commonly used to visualize and explore real-world environments. VR technology is also useful in a variety of application in university for certain course area, especially for the student who needs a practical approach to operating an appliance in a physical lab and have trouble to take a chance. Hence, the learning application for building a computer in VR, namely PC Guide is developed on the additional device such as a VR Oculus headset as the platform to visualize the part of the computer components. The target user for the proposed application is the student who takes the Computer Architecture course (BIC10503). TRES-D is used as the methodology for developing the PC Guide application. The information about computer components is obtained from research on the subject of Computer Architecture. Therefore, it can be concluded that the PC Guide application can be used as a guide for the target user.